Longitudinal Relationships among Visual Acuity and Tasks of Everyday Life: The Salisbury Eye Evaluation Study - Lam, Byron L. (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. To study the relationships among visual and physical function trajectories of aging adults. METHODS. The community-based random sample consists of 2520 adults who were aged 65 to 84 years in 1993 to 1995 and reassessed 2, 6, and 8 years later. Presenting and best-corrected Early Treatment Diabetic Retinopathy Study visual acuity were obtained. Activities of daily living (ADLs) and instrumental ADLs (IADLs) were evaluated through survey instruments. Growth curve models were used to simultaneously estimate health trajectories and obtain associations among the trajectories while controlling for relevant covariates. RESULTS. Best-corrected acuity (logMAR) worsened by an average of 0.013 (∼1 letter) annually. ADL difficulties increased by 0.22 standard deviations (SD) and IADL difficulties increased by 0.28 SD annually. Controlling for demographic and health covariates, visual acuity rates of decline correlated with rates of increase in ADL difficulties (r = 0.15, P = 0.05) and IADL difficulties (r = 0.41, P < 0.001). Acuity loss was significantly related to increases in ADLs for men (b = 0.039, P < 0.01), but not for women (b = 0.001, P > 0.9). The direct effects of acuity loss were strongest for IADLs where a 1-unit decline in acuity (logMAR) was associated with a 0.067 SD increase in IADL difficulties (P < 0.001) at baseline, and a 1-unit acuity decline (logMAR) per year resulted in a 0.10 SD unit increase in the rate of change in IADL difficulties (P < 0.001) per year. CONCLUSIONS. Over time, increases in visual acuity loss were related to increased IADL difficulties in men and women and increases in ADL difficulties for men only. The findings support the importance of maintaining vision in older adults.